Pengaruh Pemberian Pupuk Organik Cair (POC) Berbahan Limbah Ikan Terhadap Pertumbuhan Dan Hasil Tanaman Sawi (Brassica juncea L.) - Desmanto, Dipan; Susilo, Edi; Parwito, Parwito (Perkumpulan Dosen Muda (PDM) Bengkulu, 2024)
This study aims to determine the optimal dosage and concentration of fish-waste-based liquid organic fertilizer (POC) on the growth and yield of mustard greens, as well as to evaluate the interaction between these factors. The experiment was conducted using a Completely Randomized Block Design (CRBD) with a factorial pattern of 2 factors: concentration (K1: 1 liter POC + 5 liters water, K2: 1 liter POC + 10 liters water, K3: 1 liter POC + 15 liters water) and dosage (D0: control, D1: 100 ml/polybag, D2: 150 ml/polybag, D3: 200 ml/polybag). The results indicated that the D3 dosage (200 ml POC) produced the best outcomes across all growth and yield parameters for mustard greens in both planting periods. Additionally, the K1 concentration (1 liter POC + 5 liters water) also yielded the best results for various growth and yield parameters. A significant interaction between concentration and dosage was observed for plant height during the first period and for various other parameters in the second period